Coping Profiles Differentiate Psychological Adjustment in Chinese Women Newly Diagnosed With Breast Cancer. (June 2017) - Li, Lingyan; Li, Shichen; Wang, Yuping; Yi, Jinyao; Yang, Yanjie; He, Jincai; Zhu, Xiongzhao
Objective . The study aimed to explore latent profiles of coping in Chinese women newly diagnosed with breast cancer and examine the differences of psychological distress, demographic, and medical characteristics across profiles. Methods . Latent profile analysis was used to identify 3 classes of copers based on data from 618 Chinese women newly diagnosed with breast cancer who completed questionnaires assessing their coping strategies and psychological distress. Results . "Adaptive coper, " reporting most use of adaptive cognitive coping strategies, behaviors of acceptance and shifting attention, and least use of maladaptive cognitive coping strategies, had the best psychological adjustment. "Negative coper, " characterized by most use of maladaptive cognitive coping strategies, least use of adaptive cognitive coping strategies except "putting in perspective, " and median levels of medical coping behaviors, had the worst psychological adjustment. "Inconsistent coper, " with great use of all cognitive coping strategies, and most behaviors of fighting against the disease, and fewest behaviors of attention shift, had relatively high levels of psychological distress. Younger age, less education, shorter time since diagnosis, widowed, living in rural areas, and undergoing chemotherapy are possible markers for patients with less adaptive coping patterns. Conclusions . Interventions should be developed according to the different coping profiles of patients, and the key group to target is "negative copers, " who may benefit from cognitive behavioral approaches that combine emotion, cognition and behavior, which could help them more effectively appraise and cope with stressful events.